Pilot scale study on steam explosion and mass balance for higher sugar recovery from rice straw. (January 2015) - Sharma, Sandeep; Kumar, Ravindra; Gaur, Ruchi; Agrawal, Ruchi; Gupta, Ravi P.; Tuli, Deepak K.; Das, Biswapriya
Highlights: First study on process parameters for SE of rice straw by water, SA and PA. A pilot-scale batch pretreatment system was successfully developed. Effect of inhibitors and oligomers on enzymatic hydrolysis was studied. Process mass balance showed effective pretreatment using both water and SA. Total saccharification yield of 81.8% and 77.1% obtained for water and SA. Abstract: Pretreatment of rice straw on pilot scale steam explosion has been attempted to achieve maximum sugar recovery. Three different reaction media viz . water, sulfuric acid and phosphoric acid (0.5%, w/w) were explored for pretreatment by varying operating temperature (160, 180 and 200 °C) and reaction time (5 and 10 min). Using water and 0.5% SA showed almost similar sugar recovery (∼87%) at 200 and 180 °C respectively. However, detailed studies showed that the former caused higher production of oligomeric sugars (13.56 g/L) than the later (3.34 g/L). Monomeric sugar, followed the reverse trend (7.83 and 11.62 g/L respectively). Higher oligomers have a pronounced effect in reducing enzymatic sugar yield as observed in case of water. Mass balance studies for water and SA assisted SE gave total saccharification yield as 81.8% and 77.1% respectively. However, techno-economical viability will have a trade-off between these advantages and disadvantages offered by the pretreatment medium.